Effectiveness of auricular laser acupuncture on anxiety, stress, sleep quality, fatigue and muscle tension of Psychosocial Care Center professionals: a quasi-experimental pilot study - Lara Rocha Silva; Luana Vieira Toledo; Andreia Guerra Siman; Talita Prado Simão Miranda; Maria Clara Vidgal Santana; Yara Martins Rodrigues; Bruna de Oliveira Alves; Caroline de Castro Moura (Revista Brasileira de Enfermagem, 2025)
ABSTRACT Objectives: to assess the effectiveness of auricular laser acupuncture in professionals from Psychosocial Care Centers regarding anxiety, stress, sleep quality, fatigue, trapezius muscle tension threshold, satisfaction with treatment and possible adverse reactions. Methods: a quasi-experimental pilot study conducted with 24 professionals. Five auricular laser acupuncture sessions were performed. Data were collected at the beginning and end of treatment, and in a period of 15 days after the end (follow-up), analyzed by paired Wilcoxon test. Results: auricular laser acupuncture was effective in reducing levels of anxiety, stress, fatigue and improving sleep latency. There was no statistically significant difference in muscle tension threshold. Professionals were satisfied with treatment, and the occurrence of adverse reactions was not significant. Conclusions: auricular laser acupuncture triggered positive effects for all variables investigated, except for trapezius muscle tension threshold.